Seroprevalence and risk factors of hantavirus and hepatitis E virus exposure among wildlife farmers in Vietnam - Ha Thi Thanh Nguyen; Hu Suk Lee; Bett, Bernard K.; Ling, J.; Thang Nguyen-Tien; Sinh Dang-Xuan; Hung Nguyen-Viet; Unger, Fred; Lam, Steven; Vuong Nghia Bui; Tung Duy Dao; Lundkvist, Å.; et al. (2025)
Background: Wildlife farming is a growing industry, but it poses substantial risks for zoonotic disease transmission, including infections caused by hantaviruses and hepatitis E virus (HEV). This study aimed to determine seroprevalences of these viruses among wildlife farmers and identify associated risk factors.